Impacto del transporte marítimo de china y estados unidos, coyuntura de Colombia en el comercio internacional (2021)
Maritime transport is the main modality of foreign trade, 90% of the merchandise is transported by water, in Colombia, there are approximately 184 companies that provide this service distributed in different areas of the country, foreign trade operations have been decree sing since 2018. The panorama of maritime transport is in a process of transformation that is part of the transition to a new normal, in search of the economic growth of the countries, as the safest and most reliable means for the exchange of goods and services.